Pola Spasial Transformasi Wilayah di Koridor Yogyakarta-Surakarta - Giyarsih, Sri Rum (Forum Geografi, 2010)
This research is conducted in Yogyakarta-Surakarta Corridor which become an intercity corridor that has been experiencing regional transformation. The aim of this research is to analyze the pattern of regional transformation using secondary data. The research covers all of villages along Yogyakarta-Surakarta Corridor (206 villages). The data processing employs SPSS program to apply quantitative and qualitative analysis method. The result show that the higher the physical accessibility, the higher is the degree of regional transformation. This research also reveals that high regional transformation patterns which are drawn by five variables, scattered in the villages which have high physical accessibility degrees and that the villages which have low physical accessibility degrees confirm the reverse level.